Optimizing the Production and Sales Capacity of Fish Crackers in Sidoarjo, Indonesia - Emy Rosnawati; Mochammad Tanzil Multazam; Atikha Sidhi Cahyana (Universitas Muhammadiyah Sidoarjo, 2019)
This paper aims to provide additional knowledge related to increased production and marketing for fish cracker craftsmen. The method used is the method of mentoring and workshops, with partners being fish cracker craftsmen in the sawohan area of ​​Sidoarjo. The result of this assistance is an increase in production and marketing from partners.